Antimutagenic effects of subfractions of Chaga mushroom ( Inonotus obliquus) extract - Ham, Seung-Shi; Kim, Soo-Hyun; Moon, Sun-Young; Chung, Mi Ja; Cui, Cheng-Bi; Han, Eun-Kyung; Chung, Cha-Kwon; Choe, Myeon (Mutation research, 2009)
Inonotus obliquus is a mushroom commonly known as Chaga that is widely used in folk medicine in Siberia, North America, and North Europe. Here, we evaluated the antimutagenic and antioxidant capacities of subfractions of Inonotus obliquus extract . The ethyl acetate extract was separated by vacuum chromatography into three fractions, and the fraction bearing the highest antimutagenic activity was subsequently separated into four fractions by reversed phase (ODS-C 18) column chromatography. The most antimutagenic fraction was then separated into two subfractions (subfractions 1 and 2) by normal phase silica gel column chromatography. Ames test analysis revealed that the subfractions were not mutagenic. At 50 μg/plate, subfractions 1 and 2 strongly inhibited the mutagenesis induced in Salmonella typhimurium strain TA100 by the directly acting mutagen MNNG (0.4 μg/plate) by 80.0% and 77.3%, respectively. They also inhibited 0.15 μg/plate 4NQO-induced mutagenesis in TA98 and TA100 by 52.6–62.0%. The mutagenesis in TA98 induced by the indirectly acting mutagens Trp-P-1 (0.15 μg/plate) and B(α)P (10 μg/plate) was reduced by 47.0–68.2% by the subfractions, while the mutagenesis in TA100 by Trp-P-1 and B(α)P was reduced by 70.5–87.2%. Subfraction 1 was more inhibitory than subfraction 2 with regard to the mutagenic effects of 4NQO, Trp-P-1, and B(α)P. Subfractions 1 and 2 also had a strong antioxidant activity against DPPH radicals and were identified by MS, 1H NMR and 13C NMR analyses as 3β-hydroxy-lanosta-8, 24-dien-21-al and inotodiol, respectively. Thus, we show that the 3β-hydroxy-lanosta-8, 24-dien-21-al and inotodiol components of Inonotus obliquus bear antimutagenic and antioxidative activities.